Pekan Angan: Usaha Mengatasi Trauma Kekerasan pada Anak - Cyndi Sulistiawati; Yunita Ayu Nurfadilah; Huwaida Isnaeni Harisiyah; Mutiara Hanifa; Nyoman Desi Putriana; Puti Archianti (Jurnal Indonesia Mengabdi, 2019)
The phenomenon of violence against children is currently rampant and there has been no further handling of the trauma experienced by the victims, which in turn will affect the children’s behavior to become unsure and become more closed to the surrounding environment, so this activity is carried out to help victims to overcome their trauma so it will not leave negative impacts on their future. The team carried out several methods starting from sharing to find out about how far their knowledge of violence and experiences of violence they had experienced, then continued with the provision of material about verbal and nonverbal violence to children, then the team conducted evaluations to ensure the children understand the material that has been given. The result is that children begin to understand further about various kinds of verbal and nonverbal violence. In addition, children who are initially unsure and closed become more confident in public and more open to their surroundings.